2013
DOI: 10.1002/adfm.201302297
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Electronic Structure, and Charge Transport Characteristics of Naphthalenediimide‐Based Co‐Polymers with Different Oligothiophene Donor Units

Abstract: Naphthalenediimide (NDI)-based polymers co-polymerized with thienyl units are an interesting class of polymer semiconductors because of their good electron mobilities and unique film microstructure. Despite these properties, understanding how the extension of the thienyl co-monomer affects charge transport properties remains unclear. With this goal in mind, we have synthesized a series of NDI derivatives of the parent poly{[N,N′-bis(2-octyldodecyl)-naphthalene-1,4,5,8-bis(dicarboximide)-2,6-diyl]-alt-5,5′-(2,2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
75
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(83 citation statements)
references
References 70 publications
7
75
1
Order By: Relevance
“…As expected, the coefficients of the HOMO orbital are located on the SVS unit while that of the LUMO orbital is mainly positioned on the NDI unit, in good agreement with other NDI derivatives ( Figure S5, Supporting Information). [31,67] The dihedral angles between the NDI and SVS units are 47.70° and 43.78° ( Figure S5b, Supporting Information), which are larger than those reported for NDI and TVT, and NDI and bithiophene units, being 33.44° and 32.82°, and 32.88° and 40.61°, respectively. [66,68,69] The difference between the dihedral angles of these copolymers suggests a clear departure from extensive and continuous planarity in the polymer films with the most distorted being the PNDI-SVS copolymer.…”
Section: Synthesis and Density Functional Theory Calculationmentioning
confidence: 46%
See 1 more Smart Citation
“…As expected, the coefficients of the HOMO orbital are located on the SVS unit while that of the LUMO orbital is mainly positioned on the NDI unit, in good agreement with other NDI derivatives ( Figure S5, Supporting Information). [31,67] The dihedral angles between the NDI and SVS units are 47.70° and 43.78° ( Figure S5b, Supporting Information), which are larger than those reported for NDI and TVT, and NDI and bithiophene units, being 33.44° and 32.82°, and 32.88° and 40.61°, respectively. [66,68,69] The difference between the dihedral angles of these copolymers suggests a clear departure from extensive and continuous planarity in the polymer films with the most distorted being the PNDI-SVS copolymer.…”
Section: Synthesis and Density Functional Theory Calculationmentioning
confidence: 46%
“…Analogously with previous reports on PNDI2OD-T2, the two distinctive peaks observed can be attributed to a π-π* transition and an intramolecular transition with charge transfer character between the electron-donating unit and the electronacceptor unit, respectively. [63][64][65][66][67] With respect to the analogue NDI copolymer with the thienylene moiety instead of the selenophene, PNDI-SVS UV-vis absorption maxima are 30 nm red shifted owing to the introduction of a slightly stronger electron donor unit. Correspondingly, the optical band gap of PNDI-SVS, estimated at the onset of absorption maxima, is 1.31 eV, slightly narrower than the bandgap of PNDI-TVT.…”
Section: Synthesis and Density Functional Theory Calculationmentioning
confidence: 99%
“…While still not fully conclusive, there is some computational and experimental evidence that the highest mobility amorphous polymers are found in a transport regime where small polarons start becoming important. [28] In conclusion, we have shown that, at a constant level of disorder in the electronic Hamiltonian, the narrower bands present in a semiconducting co-polymer are overall beneficial to transport, i.e. the weaker coupling between states is more than compensated by a lower activation energy for transport.…”
Section: mentioning
confidence: 96%
“…24,25 The concentration of P(NDI 2 OD-T 2 ) in toluene was kept constant at 10 mg/ml throughout all measurements to achieve uniform film thicknesses across devices. The dopant solution was added to the host solution in very small amounts, ranging from 7.8 Â 10 À5 to 7.8 Â 10 À3 molar ratio (MR), which correspond to doping densities of 6 Â 10 16 to 6 Â 10 18 26,27 and previous experiments on the closely related rhodocene dimer/ P(NDI 2 OD-T 2 ) system 20,21 indicate the feasibility of the reaction, as shown in Fig. 1.…”
mentioning
confidence: 99%